Analisis Faktor Determinan Kepatuhan Pasien Diabetes Melitus Dalam Kegiatan Prolanis Diwilayah Kerja Puskesmas Paciran Kabupaten Lamongan - Arif Cholifaurrohman; Achmad Zakaria; Ade Armada Sutedja (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the determinant factors related to the compliance of Diabetes Mellitus patients in participating in Prolanis activities in the working area of ​​the Paciran Community Health Center, Lamongan Regency. This study used an observational analytical design with a cross-sectional approach. Results: The results showed that the level of knowledge, motivation, family support, support from health workers, and ease of access to health services were significantly related to patient compliance in participating in Prolanis activities. Multivariate analysis showed that family support was the most dominant factor influencing patient compliance, followed by motivation and level of knowledge. In contrast, age and gender characteristics did not show a significant relationship with patient compliance. The compliance of Diabetes Mellitus patients in participating in Prolanis activities was influenced by various factors, especially family support, motivation, and level of knowledge.